Crisis management in a complex world - Gilpin, Dawn R.; Murphy, Priscilla J.; Oxford eBooks (Oxford : Oxford University Press, 2008)
This book pairs real-world examples from across the globe with theory-based analysis to show why simplification often fails to alleviate crises, and can even intensify them. Gilpin and Murphy propose a new, complexity-based approach to organizational learning that can allow organizations to adapt quickly to new circumstances.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Crisis management; Electronic books